Foreign direct investment, trade and economic growth : challenges and opportunities - Ahmed, Shahid (London : Routledge, 2013)
This volume examines the opportunities and challenges in foreign direct investment (FDI) and trade, particularly service trade, for developing and emerging economies in a globalised world.
Includes bibliographical references and index.
Keywords: Investments, Foreign -- Developing countries; International trade